Purchasing Power Parity in the Euro Area: Evidence from Structural Break LM Test - Suluk, Seher; Tanrıseven, Kemaletttin (International Journal of Economics and Financial Issues, 2018)
Purchasing power parity (PPP) which is an indicator of price level varieties across the countries is a popular work item at the present time. This study focuses on purchasing power parity (PPP) for EU member countries which use Euro. In other words, in this study, Bulgaria, Croatia, Czech Republic, Denmark, Hungary, Latvia, Lithuania, Poland, Romania, Sweden and the United Kingdom which do not use Euro among the 28 member countries are being ignored, the study deals with 19 EU member countries which use Euro (Euro zone). These countries are Austria, Belgium, Cyprus, Estonia, Finland, France, Germany, Greece, Ireland, Italy, Latvia, Lithuania, Luxembourg, Malta, Portugal, Slovakia, Slovenia, Spain and the Netherlands. In this study, LM unit root test which is improved by Lee ve Strazicich have been perfomed for the countries in question between 2000-2016 by gauss method. Keywords: Purchasing Power Parity, Real Exchange Rate, EU Member Countries, Unit Root Test JEL Classification: F31